Genetic Monitoring of Laboratory Rodents Using Single Nucleotide Polymorphisms (Journal of Laboratory Animal Science, 2025)
Maintaining the genetic integrity of laboratory rodents is essential for achieving reliable and reproducible results in bio medical experiments. Genetic variations among laboratory animals can lead to flawed results, highlighting the impor tance of rigorous quality control testing. Among various genetic markers, single-nucleotide polymorphisms (SNPs) are  the most common and provide a dependable method for genetic monitoring due to their precision and stability. These  markers support efficient, cost-effective, and high-throughput genotyping strategies. This study aims to standardize  SNP detection as a genetic monitoring tool in laboratory rodents using the Amplification Refractory Mutation System  (ARMS) PCR. Genomic DNA was isolated from ten mouse strains: A/J, BALB/c, C3H/J, CD-1, C57BL/6, DBA/2, FVB/ NJ, Swiss Webster, Swiss/Bare, and BDF1. The DNA was obtained from tail tissue samples using the phenol–chloroform  extraction technique, followed by quantification with a Nanodrop spectrophotometer. DNA quality was assessed through  agarose gel electrophoresis. SNP markers were chosen based on polymorphisms from the Mouse Genome Informatics  (MGI) database, and primers were designed using the PRIMER1 tool. We optimized PCR conditions by systematically  varying parameters like DNA concentration, PCR cycles, annealing temperature, Taq mix concentration, and reaction  volume. We achieved reproducible amplification for selected SNP markers through methodical optimization, with 10 of  the 19 tested markers yielding clear allele distinction across strains. The ARMS PCR approach provided straightforward,  reliable genotyping without requiring restriction enzyme digestion or complex data interpretation. Our findings demon strate that ARMS PCR can be a cost-effective tool for genetic monitoring in laboratory colonies. Future work will involve  sequencing amplified products to confirm allele assignments and validate the method’s accuracy.
Keywords: Single-nucleotide polymorphism; genetic monitoring; laboratory rodent